Study Circles to Enhance Program Growth in the New York City Adult Literacy World - Barbara Heuer; Dianne Ramdeholl; Eric Appleton (Adult Education Research Conference, 2007)
The experiences of facilitators and participants in 4 study circles which focused on qualitative research points up individual, group, and systemic challenges and potential for educators in New York City literacy centers.